The Effect of Production and Capital on the Farmers’ Welfare in Klambir V Kebun Village, North Sumatra - Fadlan, Ahmad; P. Lubis, Rizal; Handoko Tarigan, Muhammad (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
The analysis of the welfare of rice farming in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency aims to analyze the factors that affect farm welfare, namely land area, production, price, education, labor, capital, government policy and technology. The population of the research were 470 rice farmers, while tha sample were 216 rice farmers as the respondents The data were processed using factor test analysis and then analyzed using multiple linear regression. Based on the data obtained from the distribution of questionnaires, the data were processed using SPSS software Version 23.0 for Windows. Based on the Confirmatory Factor Analysis (CFA), it was found that from the 8 variables analyzed with the factor analysis model consisted of 2 factors, namely production factors and capital factors. Based on the results of multiple linear regression analysis, it was found that production and capital have a significant effect on the welfare of farming in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency. Farmers need guidance from the public or private sectors regarding marketing their harvested crops and utilizing technology to enhance both the quantity and quality of their production. To become independent, farmers should also establish farmer groups or cooperatives that can assist in getting financing loans, marketing their produce, and sharing information amongst farmers.